Barbara Kruger - Thinking of you, I mean me, I mean you - Eleey, Peter ca. 20. Jh; Farrell, Robyn; Govan, Michael 1963-; Rondeau, James; Whitley, Zoe (Los Angeles County Museum of Art, 2021)
Since the mid-1970s, Barbara Kruger (born 1945) has been interrogating consumer culture in works that often combine visual and written language. In her singular graphic style, Kruger probes aspects of identity, desire and consumerism that are embedded in our everyday lives. This volume traces her continuously evolving practice to reveal how she adapts her work in accordance with the moment, site and context. The book features a range of striking images from her analogue paste-ups of the 1980s to digital productions of the last two decades, including new works produced on the occasion of the exhibition. Also featured are singular works in vinyl, her large-scale room wraps, multichannel videos, site-specific installations and commissioned works. The book also showcases how Kruger's site-specific works have been reconceived for each venue, and includes a section of reprinted texts selected by the artist. Renowned for her use of direct address and her engagement with contemporary culture, Kruger is one of the most incisive and courageous artists working today. This volume explores how her pictures and words remain urgently resonant in a rapidly changing world. Exhibition: Art Institute of Chicago, USA (25.04.-22.08.2021) / Los Angeles County Museum of Art, USA (03.10.2021?22.05.2022) / The Museum of Modern Art, New York, USA (27.02.2022?02.01.2023)
Impressum: Published in conjunction with the exhibition "BARBARA KRUGER: THINKING OF YOU. I MEAN ME. IM MEAN YOU", at the Art Institute of Chicago (April 25-August 23, 2021) and Los Angeles County Museum of Art (October 3, 2021-May 22, 2022), and a related site-specific installation at The Museum of Modern Art, New York (July 2, 2022 -January 2, 2023)
Auf dem Titelblatt sind die beiden Worte 'you' (in "Thinking of you") and 'me' durchgekreuzt
Keywords: Kruger, Barbara -- 1945-; Geschichte 1979-2020; Kruger, Barbara / 1945- / Exhibitions; Words in art / Exhibitions; Political art / United States / Exhibitions; Kruger, Barbara / 1945-; Political art; Words in art; United States; Exhibition catalogs; Ausstellungskatalog -- Art Institute of Chicago -- 25.04.2021-23.08.2021 -- Chicago, Ill.; Ausstellungskatalog -- Los Angeles County Museum of Art -- 03.10.2021-22.05.2022 -- Los Angeles, Calif.; Ausstellungskatalog -- The Museum of Modern Art -- 02.07.2022-02.01.2023 -- New York, NY